Assessment of knowledge, attitude and practice towards COVID-19 and its' psychological impact among the public of a metropolitan city of South India - Salam, Hiba; Bhat, Nuthan; Chakraborty, Ananya; Acharya, Supriya (International Journal Of Community Medicine And Public Health, 2020)
Background: Our study assessed the knowledge, attitude and practice towards COVID-19 and its’ psychological impact during the rise in COVID-19 cases and the subsequent implementation of lockdown in India. Methods: We distributed an online questionnaire to 500 people between March 2020 to April 2020. We measured knowledge about COVID-19, attitude regarding the virus, practices, preventive measures and psychological responses. Results: Out of the 500 responses, 64.6% (323) were women and 35.4% (177) were males and all the participants had completed high school. 95% (475) of the respondents had ≥75% knowledge, 86.8% (434) had positive attitudes, 98.2% (491) followed adequate preventive measures, 14.2% (71) reported moderate to extremely severe depression, 13.6% (68) reported moderate to extremely severe anxiety and 6.6% (33) reported moderate to extremely severe stress. Conclusions: Knowledge, attitude and practice scores varied across age, sex, level of education and occupation (p<0.001). Higher knowledge was found to be associated with better attitudes and practices (p=0.08). The rise in COVID-19 cases and deaths in India and the subsequent implementation of lockdown had an impact on the psychological health of the respondents. Better knowledge scores indicated better psychological health in terms of anxiety and stress but yielded higher depressive symptoms which were not statistically significant.